Learning Problems of Number Concepts in Elementary Schools - Yolanda, Yolanda; Meywanthi , Nindha Iqlima; Rahma , Sati; Sofyeni , Rezzy Apriska; Qonitah, Mutiara; Azzahra , Ghiatsya; Sari , Rulia; Arini , Dian Widityastuti; Nurhaswinda, Nurhaswinda (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to examine the challenges faced by elementary school students in understanding number concepts. The approach used is a qualitative method with a case study design. Case studies were chosen because they provide the researcher with an opportunity to explore in-depth the specific difficulties experienced by students, both in terms of concept understanding, basic principles, and verbal abilities. Focusing on one context allows for the acquisition of richer and more meaningful data regarding the challenges in learning number addition. Data collection was conducted through reviewing several journal articles, analyzing the issues, and drawing conclusions. The results of the study indicate that students often face obstacles in understanding number concepts, the principles of number addition, and in expressing their understanding verbally. Several contributing factors include a lack of precision when solving problems, failure to check answers, incorrect understanding of number formulas, inability to understand the intent of the questions, and difficulty in representing numbers visually. These findings can be used by classroom teachers as a reference to identify and address problems experienced by students. This contextual information is highly valuable in designing more effective teaching strategies to help students overcome difficulties with number concepts.